STUDY ON OCEAN CURRENT IN INDIAN OCEAN USING NUMERICAL MODEL - Duong, Pham Xuan (Vietnam Journal of Marine Science and Technology, 2014)
OpeNDAP technology (Open-source Project for a Network Data Access Protocol) is used to get access to global data for Indian Ocean region for research. The ocean currents in the Indian Ocean has been computed for many years, results show that: The strong currents exist continuously in Indian Ocean. They flow from west to east that are away from the mainland and in the range from 50S to 50N latitude, and the current near west coast has speed of over 100 cm/s. Also, in many parts of Indian Ocean there are the large synop vortices that have diameter of about hundreds of kilometers, and the speed of vortices is very great, over 100 cm/s. Over time, these vortices do not stay at the same place, but move frequently. The results by using numerical modelling are compared with NASA satellite images and have the correspondence.